1997
DOI: 10.1103/physrevd.55.5408
|View full text |Cite
|
Sign up to set email alerts
|

Quark confinement dynamics

Abstract: Starting from Buchmüller's observation that a chromoelectric flux tube meson will exhibit only the Thomas type spin-orbit interaction, we show that a model built upon the related assumption that a quark feels only a constant radial chromoelectric field in its rest frame implies a complete relativistic effective Hamiltonian that can be written explicitly in terms of quark canonical variables. The model yields linear Regge trajectories and exhibits some similarities to scalar confinement, but with the advantage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2000
2000
2002
2002

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(86 citation statements)
references
References 18 publications
(22 reference statements)
2
83
0
1
Order By: Relevance
“…In this paper we have demonstrated that a fourvector confinement interaction we found previously [11] is equivalent to scalar confinement. This vector type interaction bears a close resemblance to the QCD string, although there are significant differences.…”
Section: Conclusion and Summarysupporting
confidence: 58%
See 1 more Smart Citation
“…In this paper we have demonstrated that a fourvector confinement interaction we found previously [11] is equivalent to scalar confinement. This vector type interaction bears a close resemblance to the QCD string, although there are significant differences.…”
Section: Conclusion and Summarysupporting
confidence: 58%
“…It was pointed out by Buchmüller [2] that in the rest frame of the QCD flux tube there is no color magnetism so that the only spin orbit interaction is Thomas precession. If we want to implement Buchmüller's criterion we may assume [11] that in the quark rest frame…”
Section: The Four-vector Potential Isomorphic To the Scalar Potenmentioning
confidence: 99%
“…is accompanied by a dynamical mass generation and the loss of conformal invariance as for the non-linear sigma model or the Gross-Neveu model in 1+1 dimensions. This is indeed the case for N = 1 which represents a continuum version of the two-leg zigzag ladder [31,32] in the absence of the so-called twist perturbation [33]. However, for N ≥ 2, the interaction flows to an intermediate fixed point (g * < ∞) where the system displays critical properties with a smaller (and generally non-integer) central charge than c UV according to the Zamolodchikov c-theorem [47].…”
Section: Identification Of the Infrared Fixed Pointmentioning
confidence: 99%
“…We shall follow, in this paper, two different routes to find some CSL behaviour in the IR limit of ladder problems. On the one hand, frustration may play its role either by suppressing geometrically the backscattering contribution as in zigzag ladders [31][32][33][34] or by allowing several independent coupling constants and the possibility to eliminate the unwanted term by a fine tuning mechanism [35,11]. In that case, as we shall see later, the CSL found at this special point will be destabilized upon switching on weak backscattering contributions but there will exist an intermediate low-energy region governed by the CSL behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…[3] , , , [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] , , [24] , , n , r [25] http://cssjweb.chem.eng. …”
unclassified